Introduction to public administration in the Philippines a reader [review of] - Sajo, Thomas A. (Philippine Journal of Public Administration, 1993)
A review of the textbook entitled "Introduction to Public Administration in the Philippines: A Reader," edited by V.A. Bautista, M.C. Alfiler, D.R. Reyes, and P.D. Tapales (University of the Philippines Press and the College of Public Administration, Quezon City, 1993).